2018
DOI: 10.1101/370023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing fMRI inter-subject correlations between groups using permutation tests

Abstract: Inter-subject correlation (ISC) based analysis is a conceptually simple approach to analyze functional magnetic resonance imaging (fMRI) data acquired under naturalistic stimuli such as a movie. We describe and validate the statistical approaches for comparing ISCs between two groups of subjects implemented in the ISC toolbox, which is an open source software package for ISC-based analysis of fMRI data. The approaches are based on permutation tests. We validated the approaches using five different data sets fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 39 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Inter-subject Correlation Analysis. Inter-subject correlation (ISC) analysis was done following the methods described in previous research (Tohka, Pollick, Pajula, and Kauppi, 2019;Kauppi et al, 2014Kauppi et al, , 2010Pajula et al, 2012) using the ISC toolbox 2 . ISC was computed using an unpaired studentised between-group analysis (ASD-TD) for each movie separately and a paired between-movie analysis (Romantic-Classical) for each group separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-subject Correlation Analysis. Inter-subject correlation (ISC) analysis was done following the methods described in previous research (Tohka, Pollick, Pajula, and Kauppi, 2019;Kauppi et al, 2014Kauppi et al, , 2010Pajula et al, 2012) using the ISC toolbox 2 . ISC was computed using an unpaired studentised between-group analysis (ASD-TD) for each movie separately and a paired between-movie analysis (Romantic-Classical) for each group separately.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical Tests of ISC maps. ISCs between groups were compared with a voxel-null permutation test with subject-wise permutations (Tohka, Pollick, Pajula, and Kauppi, 2019). This test provides uncorrected p-values which were transformed into Z-values using p-to-Z transform.…”
Section: Methodsmentioning
confidence: 99%
“…Chen (2016) discusses two different permutation strategies that can be used to form a null distribution: subject-wise and element-wise permutations. Subject-wise permutation testing corresponds to the random swapping of subjects between the two groups before computing subject-pairwise ISCs, while element-wise permutation testing corresponds to exchanging the components of the correlation matrix (Tohka et al, 2018). Chen (2016) suggested that subject-wise permutations are more reliable for non-parametric statistical testing of two groups, because element-wise permutation leads to tests with excessively liberal hypothesis tests.…”
Section: Appropriate Isc Analysis Methodsmentioning
confidence: 99%
“…ISC is also used to highlight the different brain responses two different groups might have while experiencing the same stimulus (Hasson et al, 2009;Salmi et al, 2013). ISC is determined by calculating correlation coefficients between the fMRI time series of the subjects in corresponding brain locations and then averaging the coefficients (Tohka, Pollick, Pajula, & Kauppi, 2018).…”
Section: Intersubject Correlationmentioning
confidence: 99%
See 1 more Smart Citation